Clostridium butyricum MIYAIRI 588 as Adjunctive Therapy for Treatment-Resistant Major Depressive Disorder: A Prospective Open-Label Trial. Issue 5 (September 2018) - Miyaoka, Tsuyoshi; Kanayama, Misako; Wake, Rei; Hashioka, Sadayuki; Hayashida, Maiko; Nagahama, Michiharu; Okazaki, Shihoh; Yamashita, Satoko; Miura, Shoko; Miki, Hiroyuki; Matsuda, Hiroyuki; Koike, Masahiro; et al.
Abstract : Aim: Up to 60% of depressed patients do not obtain sufficient relief from a course of antidepressant therapy, and these treatment-resistant major depressive disorder (TRD) patients are at increased risk for relapse, chronicity, persistent psychosocial impairments, and suicide. Probiotics actively participate in treatment of neuropsychiatric disorders. However, the role of gut microbiota in brain disorders and depression remains unclear. We performed a prospective study to evaluate the effects of Clostridium butyricum MIYAIRI 588 (CBM588). Methods: This was an 8-week open-label study to evaluate the efficacy and safety of CBM588 in combination with antidepressants in adult patients diagnosed with TRD according to Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision . Forty antidepressant-treated inpatients were included. Patients were randomized to adjuvant treatment with CBM588 (n = 20) or control (n = 20). The primary endpoint was the change in the 17-item Hamilton Depression Rating Scale score from baseline to week 8. Secondary end points were changes in the Beck Depression Inventory and the Beck Anxiety Inventory scale scores from baseline to week 8. The Systematic Assessment of Treatment Emergent Events—General Inquiry was used to assess adverse effects. Results: CBM588 (60 mg/d) in combination with antidepressants (flvoxamine, paroxetine, escitalopram, duroxetine, and sertraline) provided significant improvement in depression. All patients completed the trial, and 70% responded to treatment; the remission rate was 35.0%. No serious adverse events occurred. Conclusions: These preliminary data suggest that CBM588 in combination with antidepressants is effective and well tolerated in the treatment of TRD. Further studies using a larger, double-blind, parallel-group design are warranted to confirm these findings.